Mempertegas Hukum dan Mengawal Pembangunan Nasional dengan Pendekatan Pers yang Humanis: (Media dan Masyarakat) - Siregar, Nurfitriani M.; Hidayat, Arifin; Marlina, Marlina; Lubis, Nurul Fadilah (Program Fakultas Dakwah dan Ilmu Komunikasi (FDIKOM), UIN Syarif Hidayatullah Jakarta, 2023)
Law enforcement has a positive impact on the state as well as on society, in the law enforcement process it is also based on justice without discrimination, in looking at the perpetrators of criminal law, but in general there are still some people who are not satisfied with the implementation of law enforcement in Indonesia, both aspects of justice as well as the usefulness of the law implemented in the community. So law enforcement must also look at the humanist aspect, of course this can be done by members of the press through the existing media. The purpose of this study is to describe humanist law enforcement through the media and society. The research methodology uses a qualitative approach with descriptive analysis methods. The research results show as Press. The media has a role as a vessel for enlightenment, reporting with a humanist perspective, community empowerment in law enforcement, and also the press must have responsible journalistic ethics.